Hubungan Konsep Diri Dan Interaksi Teman Sebaya Dengan Prokrastinasi Akademik Mahasiswa - Nurwahyuni, Isna, Dr. Taufik, M.Si (2015)
This research aim to know the relationship between self concept and peers interaction of academic procrastination student'. The subjek in this study are the student' in eight semesters or being a thesis at the Muhammadiyah Universitas Surakarta as much as 114 respondents. The hipothesis tested was there is a connection between self concept and peer interaction with academic procrastination. The technique of sampling use incidental sampling. Data collection is carried out by three scales, is the scale of the academic procrastination, the self concept and peer interaction. The statistical analysis used in this study were multipel linier regression analysis. Statistical analysis result obtained that there is a significant relationship between self concept and peer interaction with academic procrastination. The effective contribution of the self concept and peer interaction agains academic procrastination is 15%. The result of this research showed there was a significant relationship between self concept and peer interaction with academic procrastination. The conclusion of relationship self concept and peer interaction are negatif toward academic procrastination. That is, if self concept and peer interaction is higher, so academic procrastination student' will go down. The implication of this research in the field of education is an academic procrastination can be reduced by improving the self concept and peer interaction. Self concept give a framework of thinking that determine how to process the information abaut yourself is good from a physical aspect, psychic aspect, sosial aspects, moral and family aspects, so that student' have the self motivation, emotional stability and trust on the capability of self finishing academic assignments. In addition the high peer interaction as a function of the information source and motivation can give good influence for student' in finishing academic assignments.